The relationship between soil pH and selected soil properties in 48 years logged-over forest - A., Mohd Aizat; Mohamad Kasim, Mohamad Roslan; Sulaiman, Wan Nor Azmin; Karam Singh, Daljit Singh (Integrated Publishing Association, 2014)
Selectively logged occur at Ayer Hitam Forest Reserve starting from 1936 to 1965. The geology of this forest is made of igneous rocks with granite which is a common acid rock as its main component that may probably affect the soil properties. The relationship between soil pH with selected soil biological and chemical properties were investigated. Results showed that, the selected soil properties related mostly in the form of power function where the best simple linear regression model for soil microbial biomass C, soil microbial biomass N and total Fe with soil pH were (ln (Biomass C) = 4.534 ln (Soil pH), with = 0.996) (ln (Biomass N) = 3.035 ln ( Soil pH), = 0.994) and (ln (Iron) = 4.121 ln (Soil pH), 0.996 respectively. However, it has a negative relationship with soil electrical conductivity as the best in the equation was (ln (Soil EC) = -1.037 ln (Soil pH), 0.973). The amount of copper content in the soil is related positively in the form of logarithmic function with soil pH (Copper = 0.877 ln (Soil pH), 0.621).This work has establish clear relationship between soil pH with selected soil properties in acidic soil condition.